A method for preparing a black high-emission composite ceramic coating on a magnesium alloy surface
A micro-arc oxidation process with an aluminum salt-copper salt-tungsten salt system forms a black high-emissive composite ceramic coating on magnesium alloys, addressing toxicity and emissivity issues, enhancing hardness and corrosion resistance for aerospace and electronic applications.
Patent Information
- Application Number
- CN202211553796.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-06
AI Technical Summary
Existing methods for preparing black ceramic coatings on magnesium alloys using vanadium, iron, or copper salts as colorants suffer from toxicity, poor film quality, and low infrared emissivity, limiting their application in aerospace and electronic products.
A micro-arc oxidation process using an aluminum salt-copper salt-tungsten salt system electrolyte forms a black high-emissive composite ceramic coating with a spinel structure MgAl2O4 phase, enhanced by WO3 formation, improving hardness, wear resistance, and infrared emissivity.
The coating achieves a continuous, dense structure with reduced pores, high corrosion resistance, and infrared emissivity of 0.84, suitable for aerospace and electronic applications.
Smart Images

Figure CN115838956B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy surface treatment, and in particular relates to a method for preparing a black high-emission composite ceramic coating on the surface of a magnesium alloy. Background Art
[0002] Magnesium alloys are widely used in defense industries and civilian fields such as aerospace, transportation, communication equipment housings, 3C electronic products, etc. due to their high specific stiffness, specific strength, good shock absorption, excellent processing performance and good electromagnetic shielding performance. They are considered to be green engineering materials in the 21st century. However, the poor chemical stability, low electrode potential and poor corrosion resistance of magnesium alloys greatly limit their application. Therefore, magnesium alloy products usually need to be treated with surface protection before they can be put into industrial applications. In recent years, micro-arc oxidation technology has been used to treat the surface of magnesium alloy products at home and abroad, and certain progress has been made. Micro-arc oxidation technology has become an important method for surface protection treatment of magnesium alloy products at home and abroad due to its simple process, low cost, low impact on the environment, strong applicability to complex workpieces, excellent film-base bonding performance, and excellent wear resistance and corrosion resistance.
[0003] In recent years, with the development of technology in the field of aerospace, the preparation of black ceramic coatings with excellent thermal control properties on the surface of magnesium alloys by micro-arc oxidation technology has gradually attracted the attention of researchers. This coating not only has the excellent wear resistance and corrosion resistance of micro-arc oxidation coatings, but also has surface decorativeness and good thermal control properties. It has broad application prospects in spacecraft and 3C electronic products. At present, some reports on the preparation of micro-arc oxidation black coatings on magnesium alloys use vanadium salts as colorants, but vanadium salts are toxic and have certain harm to the human body; some use iron salts as colorants, but iron salts are severely ablated when oxidized on the surface of magnesium alloys, and the film quality is poor; and copper salts are used as colorants. Only a single copper salt is involved in the coloring. Although a black film can be prepared, the infrared emissivity of the film is not high. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a black high-emissive composite ceramic coating on the surface of a magnesium alloy in view of the deficiencies of the above-mentioned prior art. The method uses a micro-arc oxidation process and an aluminum salt-copper salt-tungsten salt system solution as an electrolyte to in-situ prepare a black high-emissive composite ceramic coating on the surface of an AZ31B magnesium alloy. The aluminum salt in the electrolyte is used as the main film-forming salt to form a spinel structure MgAl2O4 phase with a higher Mohs hardness in the composite ceramic coating, which significantly improves the hardness, wear resistance and corrosion resistance of the composite ceramic coating. The tungsten salt colorant is used to form WO3 to improve the infrared emissivity of the composite ceramic coating, which solves the problems of toxic colorants, poor quality of the prepared coating and low infrared emissivity.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a black high-emission composite ceramic coating on the surface of a magnesium alloy, characterized in that the specific process of the method is: using a hanger to clamp the pretreated AZ31B magnesium alloy and placing it in an oxidation tank of a micro-arc oxidation equipment, so that the pretreated AZ31B magnesium alloy is completely immersed in the aluminum salt-copper salt-tungsten salt system electrolyte in the oxidation tank as an anode, using a stainless steel sheet as a cathode, setting the power supply to a constant voltage working mode for micro-arc oxidation treatment, and preparing a black high-emission composite ceramic coating on the surface of the AZ31B magnesium alloy.
[0006] The present invention adopts a micro-arc oxidation process and uses an aluminum salt-copper salt-tungsten salt system solution as an electrolyte to prepare a black high-emission composite ceramic coating on the surface of the AZ31B magnesium alloy through an electrochemical reaction. Compared with conventional phosphoric acid-based and silicate-based electrolytes, the aluminum salt component in the aluminum salt-copper salt-tungsten salt system solution of the present invention forms a black high-emission composite ceramic coating with a spinel structure MgAl2O4 phase having a Mohs hardness of up to 8 and existing on the surface of the AZ31B magnesium alloy through an electrochemical reaction of micro-arc oxidation. The hardness and wear resistance of the spinel structure MgAl2O4 phase are better than those of the Mohs hardness. The periclase structure MgO phase with a hardness of 6 significantly improves the hardness, wear resistance and corrosion resistance of the black high-emissivity composite ceramic coating. At the same time, the copper salt component in the aluminum salt-copper salt-tungsten salt system solution ensures the formation of the black coating. The synergistically added tungsten salt component further improves the density of the black high-emissivity composite ceramic coating, making the pore size of the composite ceramic coating smaller and the holes reduced, thereby improving the corrosion resistance. The tungsten salt component is micro-arc oxidized to generate WO3. The presence of WO3 has a significant deepening effect on the colored composite ceramic layer, thereby improving the infrared emissivity of the black high-emissivity composite ceramic coating.
[0007] The above-mentioned method for preparing a black high-emissive composite ceramic coating on the surface of a magnesium alloy is characterized in that the pretreatment process of the AZ31B magnesium alloy is: 180#, 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper are used to polish the AZ31B magnesium alloy step by step, and then ultrasonically degrease the AZ31B magnesium alloy in a neutral metal cleaning solution at room temperature for 5 minutes, and use hot water and cold water to clean the surface of the AZ31B magnesium alloy respectively, and then ultrasonically clean it in anhydrous ethanol for 5 minutes to 10 minutes and then dry it.
[0008] The above-mentioned method for preparing a black high-emission composite ceramic coating on the surface of a magnesium alloy is characterized in that the preparation process of the aluminum salt-copper salt-tungsten salt system electrolyte is: adding a complexing agent, a coloring agent, a main film-forming agent, and an auxiliary film-forming agent to deionized water in sequence, and continuously stirring until completely dissolved, to prepare an aluminum salt-copper salt-tungsten salt system electrolyte with a pH value of 10 to 12; the complexing agent in the aluminum salt-copper salt-tungsten salt system electrolyte is potassium sodium tartrate with a concentration of 2g / L, the coloring agent is copper sulfate and sodium tungstate, wherein the concentration of copper sulfate is 1g / L to 2g / L, the concentration of sodium tungstate is 5g / L, the main film-forming agent is sodium aluminate with a concentration of 10g / L, and the auxiliary film-forming agent is sodium fluoride with a concentration of 1g / L. The present invention controls the concentration of the complexing agent to be close to that of the copper ions, utilizes the complexing agent to complex the copper ions to prevent the copper ions from precipitating in the alkaline solution, controls the concentration of the coloring agent to be relatively low to ensure that the substrate will not be ablated during high-voltage oxidation, controls the concentration of the main film-forming agent sodium aluminate to effectively reduce the arc starting voltage of micro-arc oxidation, and helps the growth of the composite ceramic coating, controls the concentration of the auxiliary film-forming agent sodium fluoride to generate magnesium fluoride during the micro-arc oxidation process, and improves the density of the composite ceramic coating.
[0009] The above-mentioned method for preparing a black high-emission composite ceramic coating on the surface of a magnesium alloy is characterized in that the power supply is a constant-voltage DC pulse power supply. The present invention promotes the composite ceramic coating to grow more densely in the early stage of micro-arc oxidation by adopting a constant-voltage DC pulse power supply and controlling the voltage in the low-voltage area.
[0010] The above-mentioned method for preparing a black high-emission composite ceramic coating on the surface of a magnesium alloy is characterized in that the process parameters of the micro-arc oxidation treatment are: voltage 500V, frequency 500Hz, duty cycle 15%, oxidation treatment time 15min~20min, and a refrigerator is used to control the temperature of the aluminum salt-copper salt-tungsten salt system electrolyte during the micro-arc oxidation treatment to be 18℃~25℃. The present invention ensures the preparation thickness of the composite ceramic coating by controlling the process parameters of the micro-arc oxidation treatment, avoids the composite ceramic coating from being ablated and having a rough surface, and achieves the best performance of the composite ceramic coating; the present invention avoids the composite ceramic coating from being ablated, having a rough surface, or even having large-diameter holes at high temperatures, which affects its corrosion resistance, by controlling the temperature of the electrolyte during the micro-arc oxidation treatment.
[0011] Compared with the prior art, the present invention has the following advantages:
[0012] 1. The present invention uses a micro-arc oxidation process and an aluminum salt-copper salt-tungsten salt system solution as an electrolyte to in-situ prepare a black high-emission composite ceramic coating on the surface of AZ31B magnesium alloy. The aluminum salt component in the electrolyte is used to form a spinel structure MgAl2O4 phase with a higher Mohs hardness, which exists in the composite ceramic coating, thereby significantly improving the hardness, wear resistance and corrosion resistance of the black high-emission composite ceramic coating.
[0013] 2. By adding tungsten salt to the aluminum salt-copper salt-tungsten salt system solution of the present invention, the density of the black high-emission composite ceramic coating is improved, the pore size is reduced, and the number of holes is reduced, thereby improving the corrosion resistance. At the same time, it has a significant deepening effect on the colored composite ceramic layer, thereby improving the infrared emissivity of the black high-emission composite ceramic coating.
[0014] 3. The black high-emission composite ceramic coating prepared in situ on the surface of AZ31B magnesium alloy by the present invention has a continuous and dense structure without through holes and good corrosion resistance (corrosion current density can reach 1.415×10 -8 A / cm 2 ), the infrared emissivity can reach 0.84.
[0015] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a surface scanning electron microscope image of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Example 1 of the present invention.
[0017] Figure 2 This is a scanning electron microscope image of the cross section of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Example 1 of the present invention.
[0018] Figure 3 This is a surface scanning electron microscope image of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Example 2 of the present invention.
[0019] Figure 4 This is a scanning electron microscope image of the cross section of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Example 2 of the present invention.
[0020] Figure 5 This is an electrochemical polarization curve diagram of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention in a 3.5% NaCl solution.
[0021] Figure 6a This is the XPS spectrum of the Al element in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention.
[0022] Figure 6b This is the XPS spectrum of the Cu element in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention.
[0023] Figure 6c This is the XPS spectrum of the Mg element in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention.
[0024] Figure 6d This is the XPS spectrum of the O element in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention.
[0025] Figure 6e This is the XPS spectrum of the W element in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0026] Example 1
[0027] This embodiment includes the following steps:
[0028] Step 1, select an AZ31B magnesium alloy sheet with a size (length × width × thickness) of 15mm × 15mm × 3mm, first use 180# water-resistant abrasive paper to polish and remove machining marks on the surface of the AZ31B magnesium alloy sheet, then use 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper to polish the AZ31B magnesium alloy step by step, ultrasonically degrease in a neutral metal cleaning solution at room temperature for 5 minutes, use hot water and cold water to clean the surface of the AZ31B magnesium alloy respectively, and then ultrasonically clean it in anhydrous ethanol for 10 minutes and then dry it for standby use to complete the pretreatment;
[0029] Step 2: Add the complexing agent, coloring agent, main film-forming agent and auxiliary film-forming agent to deionized water in sequence, and continue stirring until completely dissolved, to prepare an aluminum salt-copper salt-tungsten salt system electrolyte with a pH value of 10 to 12; the complexing agent in the aluminum salt-copper salt-tungsten salt system electrolyte is potassium sodium tartrate with a concentration of 2g / L, the coloring agent is copper sulfate and sodium tungstate, wherein the concentration of copper sulfate is 1g / L, the concentration of sodium tungstate is 5g / L, the main film-forming agent is sodium aluminate with a concentration of 10g / L, and the auxiliary film-forming agent is sodium fluoride with a concentration of 1g / L;
[0030] Step three, use a hanger to clamp the pretreated AZ31B magnesium alloy and place it in the oxidation tank of the micro-arc oxidation equipment, so that the pretreated AZ31B magnesium alloy is completely immersed in the aluminum salt-copper salt-tungsten salt system electrolyte in the oxidation tank as an anode, and a stainless steel sheet is used as a cathode. The power supply is set to a constant voltage DC pulse power supply, and the micro-arc oxidation treatment is performed in a constant voltage working mode to prepare a black high-emission composite ceramic coating on the surface of the AZ31B magnesium alloy, and an AZ31B magnesium alloy with a black high-emission composite ceramic coating on the surface is obtained; the process parameters of the micro-arc oxidation treatment are: voltage 500V, frequency 500Hz, duty cycle 15%, oxidation treatment time 20min, and a refrigerator is used to control the temperature of the aluminum salt-copper salt-tungsten salt system electrolyte during the micro-arc oxidation treatment to 18°C~25°C.
[0031] The black high-emission composite ceramic coating prepared on the surface of AZ31B magnesium alloy in this embodiment was subjected to energy spectrum EDS analysis, and the results are shown in Table 1 below.
[0032] Table 1
[0033] element Mg Al O Cu F W Total Atomic ratio (%) 21.65 24.55 44.72 4.04 2.44 2.60 100
[0034] As can be seen from Table 1, the black high-emissive composite ceramic coating prepared on the surface of AZ31B magnesium alloy in this embodiment is composed of elements such as Mg, Al, O, Cu, F, and W.
[0035] The infrared emissivity test was performed on the AZ31B magnesium alloy having a black high-emissivity composite ceramic coating on the surface in this embodiment. The test result showed that the infrared emissivity of the black high-emissivity composite ceramic coating was 0.8.
[0036] Figure 1 The surface scanning electron microscope image of the AZ31B magnesium alloy with a black high-emission composite ceramic coating on the surface of this embodiment is shown in FIG. Figure 1 It can be seen that the micropores of the black high-emissivity composite ceramic coating have a smaller pore size, which helps to improve the corrosion resistance of the composite ceramic coating.
[0037] Figure 2 This is a cross-sectional scanning electron microscope image of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in this embodiment. Figure 2 It can be seen that the black high-emissivity composite ceramic coating is tightly bonded to the AZ31B magnesium alloy substrate, and there are no through holes in the black high-emissivity composite ceramic coating, indicating that the composite ceramic coating has good corrosion resistance.
[0038] Example 2
[0039] This embodiment includes the following steps:
[0040] The difference between this embodiment and implementation 1 is that the concentration of copper sulfate in the electrolyte in step 2 is 2 g / L, and the oxidation treatment time is 15 min.
[0041] The black high-emission composite ceramic coating prepared on the surface of AZ31B magnesium alloy in this embodiment was subjected to energy spectrum EDS analysis, and the results are shown in Table 2 below.
[0042] Table 2
[0043] element Mg Al O Cu F W Total Atomic ratio (%) 20.52 25.96 42.73 6.27 1.78 2.74 100
[0044] It can be seen from Table 2 that the black high-emission composite ceramic coating prepared on the surface of AZ31B magnesium alloy in this embodiment is composed of elements such as Mg, Al, O, Cu, F, and W. Compared with Table 1 in Example 1, the Cu element content in the black high-emission composite ceramic coating increases with the increase of copper sulfate concentration.
[0045] The infrared emissivity test was performed on the AZ31B magnesium alloy having a black high-emissivity composite ceramic coating on the surface in this embodiment. The test result showed that the infrared emissivity of the black high-emissivity composite ceramic coating was 0.83.
[0046] Figure 3 The surface scanning electron microscope image of the AZ31B magnesium alloy with a black high-emission composite ceramic coating on the surface of this embodiment is shown in FIG. Figure 3 It can be seen that there are only a very small number of micropores in the black high-emission composite ceramic coating and the pore size is small.
[0047] Figure 4 This is a cross-sectional scanning electron microscope image of the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in this embodiment. Figure 4 It can be seen that the black high-emissivity composite ceramic coating is tightly bonded to the AZ31B magnesium alloy substrate, and the black high-emissivity composite ceramic coating is highly dense and has no through holes, indicating that the composite ceramic coating has good corrosion resistance.
[0048] Figure 5 The electrochemical polarization curve of the AZ31B magnesium alloy with a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention in a 3.5% NaCl solution is shown in FIG. Figure 5 It is calculated that the corrosion current I of the black high-emission composite ceramic coating in Example 1 is corr =1.052×10 -5 A / cm 2 , which is 2.582×10 -4 A / cm 2The corrosion current I of the black high-emission composite ceramic coating in Example 2 is reduced by one order of magnitude, indicating that the corrosion resistance of the black high-emission composite ceramic coating is good. corr =2.595×10 -6 A / cm 2 , the corrosion current of the black high-emission composite ceramic coating is lower than that in Example 1, indicating that the black high-emission composite ceramic coating prepared by using a higher concentration of copper salt in Example 2 has better corrosion resistance.
[0049] Figure 6a to Figure 6e The XPS spectra of Al, Cu, Mg, O and W in the AZ31B magnesium alloy having a black high-emission composite ceramic coating on the surface in Examples 1 and 2 of the present invention are shown in FIG. Figure 6a to Figure 6e It can be seen that the main components of the black high-emission composite ceramic coating in Examples 1-2 are WO3, CuO, CuAl2O4, MgAl2O4, MgO and MgF2.
[0050] In summary, the above are only preferred embodiments of the present invention and do not limit the present invention in any way. Any simple modification, change and equivalent changes made to the above embodiments according to the technical essence of the invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a black high-emission composite ceramic coating on a magnesium alloy surface, characterized in that: The specific process of the method is as follows: the pretreated AZ31B magnesium alloy is clamped by a hanger and placed in an oxidation tank of a micro-arc oxidation device, so that the pretreated AZ31B magnesium alloy is completely immersed in an aluminum salt-copper salt-tungsten salt system electrolyte in the oxidation tank as an anode, a stainless steel sheet is used as a cathode, and a power supply is set to a constant voltage working mode for micro-arc oxidation treatment, so as to prepare a black high-emission composite ceramic coating on the surface of the AZ31B magnesium alloy; The preparation process of the aluminum salt-copper salt-tungsten salt system electrolyte is: adding a complexing agent, a coloring agent, a main film-forming agent, and an auxiliary film-forming agent to deionized water in sequence, and continuously stirring until completely dissolved, to prepare an aluminum salt-copper salt-tungsten salt system electrolyte with a pH value of 10 to 12; the complexing agent in the aluminum salt-copper salt-tungsten salt system electrolyte is potassium sodium tartrate with a concentration of 2g / L, the coloring agent is copper sulfate and sodium tungstate, wherein the concentration of copper sulfate is 1g / L to 2g / L, the concentration of sodium tungstate is 5g / L, the main film-forming agent is sodium aluminate with a concentration of 10g / L, and the auxiliary film-forming agent is sodium fluoride with a concentration of 1g / L.
2. The method for preparing a black high-emission composite ceramic coating on a magnesium alloy surface according to claim 1, characterized in that: The pretreatment process of the AZ31B magnesium alloy is as follows: 180#, 600#, 800#, 1200#, 1500# water-resistant abrasive paper and metallographic sandpaper are used to polish the AZ31B magnesium alloy step by step, and then ultrasonically degrease the alloy in a neutral metal cleaning solution at room temperature for 5 minutes, and clean the surface of the AZ31B magnesium alloy with hot water and cold water respectively, and then ultrasonically clean the alloy in anhydrous ethanol for 5 minutes to 10 minutes and then dry the alloy.
3. The method for preparing a black high-emission composite ceramic coating on a magnesium alloy surface according to claim 1, characterized in that: The power supply is a constant voltage DC pulse power supply.
4. The method for preparing a black high-emission composite ceramic coating on a magnesium alloy surface according to claim 1, characterized in that: The process parameters of the micro-arc oxidation treatment are: voltage 500V, frequency 500Hz, duty cycle 15%, oxidation treatment time 15min-20min, and a refrigerator is used to control the temperature of the aluminum salt-copper salt-tungsten salt system electrolyte during the micro-arc oxidation treatment to 18°C-25°C.
